Female Servants in Early Modern England - Charmian Mansell (Oxford University Press, 2024)
What was it like to be a woman in service in early modern England? More fundamentally, who were these women? Where did they come from? In what kinds of households did they work and what were they hired to do? How did their lives intersect with the local communities in which they lived? Female Servants in Early Modern England answers these questions by exploring over 1000 witness testimonies from English church courts which record the experiences of women in service between 1532 and 1649. Drawing a wide circle around the experiences of women in service, this book analyses their lives from demographic, geographical, economic, and social perspectives. Combining quantitative and qualitative analysis of evidence, Female Servants in Early Modern England challenges our understanding of service in several key ways. These women, it argues, were intrinsic to the economy, contributing their labour to a range of types of work. Despite being itinerant workers, they were nonetheless embedded in social networks and communities. Though service is seen as a rigid institution designed to regulate labour and youth, this book shows it to have been contingent, operating with a flexibility unsanctioned by law and policy makers but nonetheless accepted within early modern society.
Keywords: 940; servants church courts witness testimony early modern women